Thermal Activated Elements Redistribution between Two-Component Coating and Substrate; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Kryukova O. N. Olga Nikolaevna (Numerical Simulation of Physical and Chemical Processes, 2016)
Title screen